College of Management and Economics, Deb. Of Statistic, Mustansiriyah University (Journal of the College of Basic Education, 2022)
There are statistical evidence that has spread tremendously since recently to explain, reduce and interpret spatial data, for example, when a disease is studied, whether this disease is on humans or animals, it requires interpretation of the spatial data resulting from this disease, as it includes observations of spatial units, for example, countries or provinces. ..etc, all of these are linked to certain points or locations.The study uses the greatest possibility method to estimate the parameters of the general spatial regression model by employing the model to study in light of the effect of spatial juxtaposition, and by using the juxtaposition of Queen, and to ensure the performance of the method of estimating the model used in this research, the simulation method was used, according to the simulation method, a program was designed in a language Matlab. In the end, it was concluded that the modified Queen's neighborhood criterion is the best, and the larger samples are taken, the better the estimate is made